Salience : multidisciplinary perspectives on its function in discourse - Chiarcos, Christian; Claus, Berry; Grabski, Michael (Trends in linguistics. Studies and monographs, 2011)
Salience refers to the prominence of information; salient items pop out and capture attention. This volume addresses the role of salience in discourse. It illustrates the range of multidisciplinary approaches - their diversities and similarities. The collection of papers covers a variety of research with different foci ranging from discourse entities, to discourse segments, to extra-linguistic factors.